Article comprising surface-treated substrate with organosilicon compound, prepreg, printed wiring board, and aqueous solution of organosilicon compound
Surface treatment of substrates with organosilicon compounds addresses the issues of dielectric loss tangent and mechanical properties in glass cloths and fillers, resulting in improved prepregs and printed wiring boards with enhanced adhesion and dielectric performance.
Patent Information
- Application Number
- JP2023120828
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2043-07-25
AI Technical Summary
Existing silane coupling agents used in surface treatment of glass cloths and inorganic fillers for printed wiring boards suffer from increased dielectric loss tangent due to amino groups, and there is a need for improved mechanical and dielectric properties, particularly in prepregs and printed wiring boards.
Surface treatment of substrates such as silica particles and glass fibers with organosilicon compounds having specific structures, enhancing adhesion with matrix resins and improving mechanical and dielectric properties.
The use of organosilicon compounds with specific structures improves the mechanical and dielectric properties of prepregs and printed wiring boards, enhancing adhesion and reducing dielectric loss tangent.
Smart Images

Figure 2025017672000001 
Figure 2025017672000002 
Figure 2025017672000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an article including a substrate surface-treated with an organosilicon compound, a prepreg, a printed wiring board, and an aqueous solution containing an organosilicon compound. [Background technology]
[0002] Silane coupling agents are compounds that have both a moiety that is reactive with inorganic substances (a hydrolyzable group bonded to a silicon atom) and a moiety that can impart various functions, such as reactivity with organic substances, solubility, and radical polymerizability, in a single molecule. They act as adhesion aids at the interface between inorganic and organic substances, and as resin modifiers for inorganic-organic composite materials, and are therefore widely used as composite resin modifiers. Among these, in recent years, it has been used for surface treatment of inorganic fillers such as silica and glass fiber products such as glass cloth, and various properties are improved by incorporating the surface-treated articles into resins. Surface treatment may involve coating the substrate with the silane coupling agent itself, or it may involve treatment with a solution to achieve uniform treatment. When using a solution, it is important to be able to handle the agent as an aqueous solution without using a solvent such as methanol, particularly from the perspective of reducing the environmental impact.
[0003] On the other hand, with the development of digital technology, electronic devices such as tablet terminals and smartphones are becoming lighter, thinner, smaller, and more functional. For example, printed wiring boards, which are one of the important components of these devices, need to be highly densely mounted and lighter, thinner, smaller, and more compact. To meet this demand, there is a strong need to improve the properties of inorganic fillers and glass cloth, which are essential components used as reinforcing materials for printed wiring boards. Furthermore, as computers, mobile devices, and communication infrastructure become faster and faster, there is a demand for inorganic fillers and glass cloth used in printed wiring boards to have improved dielectric properties to reduce transmission loss and improved tensile properties. In addition, it is preferable to highly fill the inorganic filler in order to improve the properties of the resin, and the filling rate is improved by treating the resin with various silane coupling agents. However, there is a demand for improvement to achieve even higher filling rates.
[0004] In order to meet the above-mentioned requirements for properties, inorganic fillers and glass cloth are treated with a silane coupling agent having a specific structure. In particular, in a prepreg containing glass cloth, the wettability and adhesion between the matrix resin and the glass cloth are important, and for example, when a prepreg is produced using an epoxy resin and glass cloth, these properties are improved by using glass cloth treated with a silane coupling agent.
[0005] Various surface-treated glass cloths have been proposed so far. Patent Document 1 proposes a glass cloth made of glass yarns that have been surface-treated with a silane coupling agent having an unsaturated double bond, and it has been reported that prepregs and printed wiring boards using this glass cloth have excellent insulation reliability.
[0006] Patent Document 2 proposes a glass cloth that is surface-treated with a silane coupling agent having at least one organic functional group, which is an amino group and an unsaturated double bond, and reports that prepregs and printed wiring boards using this glass cloth have low moisture absorption, excellent heat resistance, and excellent insulation reliability.
[0007] However, both of Patent Documents 1 and 2 use a silane coupling agent having an amino group, which tends to increase the dielectric tangent due to the polarity of the amino group. In addition, there is also room for improvement in the tensile properties of the glass cloth.
[0008] On the other hand, Patent Documents 3 and 4 report that the dielectric properties, heat resistance, and moist heat resistance of a resin can be improved by using a filler treated with an alkenyl group-containing silane coupling agent that does not contain polar atoms such as N atoms or O atoms. However, there is still room for improvement. In particular, long-chain alkenylsilanes having carbon numbers of 6 or 8, for example, have low hydrophilicity, which means that they require the use of alcohol in combination when forming an aqueous solution, and the storage stability of the aqueous solution is low. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2018-127747 A [Patent Document 2] JP 2019-81987 A [Patent Document 3] Patent No. 6684822 [Patent Document 4] International Publication No. 2019 / 103082 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an article, a prepreg, and a printed wiring board that are excellent in mechanical properties and insulation reliability. [Means for solving the problem]
[0011] Means for Solving the Problems The present inventors conducted extensive research to solve the above problems and discovered that an article having a substrate surface-treated with an organosilicon compound having a specific structure has excellent adhesion to matrix resins used in prepregs and printed wiring boards, in particular, and can therefore improve the mechanical properties and dielectric properties of prepregs and printed wiring boards, thereby completing the present invention.
[0012] That is, the present invention provides [1] An article comprising a substrate surface-treated with one or more organosilicon compounds selected from those represented by the following formulas (1) to (7): [ka] (In the formula, R 1 are each independently an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms, R 2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an acyl group having 1 to 20 carbon atoms, and n is an integer of 0 to 2. [2] The article according to [1], wherein the substrate is an inorganic material. [3] The article according to [2], wherein the inorganic material is silica particles or glass fibers. [4] [3] A prepreg comprising the article according to the present invention and a matrix resin. [5] [4] A printed wiring board comprising the prepreg according to the present invention. [6] An aqueous solution in which one or more organic silicon compounds selected from the organic silicon compounds represented by the following formulas (1) to (7) are dissolved in water: [ka] (In the formula, R 1 are each independently an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms, R 2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an acyl group having 1 to 20 carbon atoms, and n is an integer of 0 to 2. to provide. Effect of the Invention
[0013] According to the present invention, articles such as inorganic fillers and glass cloths treated with an organosilicon compound having a specific structure improve the properties of a resin when blended with the resin, and in particular, when combined with a matrix resin to form a prepreg, the articles impart excellent dielectric properties and tensile properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be specifically described below. [Goods] The article according to the present invention comprises a substrate that has been surface-treated with one or more organosilicon compounds selected from those represented by the following formulas (1) to (7) (hereinafter simply referred to as compounds (1) to (7)).
[0015] [ka]
[0016] (1) Organosilicon compounds In the above formulas, R 1 are each independently an alkyl group having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms, preferably 6 to 8 carbon atoms; R 2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, preferably 2 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, preferably 6 to 8 carbon atoms, or an acyl group having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, and n is an integer of 0 to 2.
[0017] R 1 and R 2 The alkyl group having 1 to 10 carbon atoms may be linear, branched, or cyclic, and specific examples thereof include methyl, ethyl, n-propyl, i-propyl, n-butyl, isobutyl, s-butyl, t-butyl, n-pentyl, neopentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups. R 1 and R 2 Specific examples of the aryl group having 6 to 10 carbon atoms include phenyl, tolyl, xylyl, α-naphthyl, and β-naphthyl groups. R 2 Specific examples of the alkenyl group having 2 to 10 carbon atoms include vinyl, allyl, and propenyl groups. R 2 Specific examples of the acyl group having 1 to 20 carbon atoms include formyl, acetyl, and propionyl groups. Among these, R 1 and R 2 As the alkyl group, a linear alkyl group having 1 to 3 carbon atoms is preferable, and a methyl group or an ethyl group is more preferable.
[0018] The organosilicon compounds represented by the above formulas (1) to (7) can be produced by known methods, for example, by reacting one of the carbon-carbon double bonds of isoprene with a hydrogen atom (Si-H group) bonded to a silicon atom of a hydrosilane such as trimethoxyhydrosilane in the presence of a metal catalyst (hydrosilylation), but the production method is not limited to this.
[0019] Specific examples of hydrosilanes include trimethoxyhydrosilane, triethoxyhydrosilane, methyldimethoxyhydrosilane, methyldiethoxyhydrosilane, ethyldimethoxyhydrosilane, and ethyldiethoxyhydrosilane.
[0020] The ratio of isoprene to hydrosilane used in the reaction is not particularly limited, but is preferably 0.4 mol or more and less than 1.5 mol, and more preferably 0.6 mol or more and less than 1.2 mol, of hydrosilane per 1 mol of the isoprene compound.
[0021] The metal catalyst used in the above reaction is not particularly limited, and examples thereof include platinum compound-containing catalysts, rhodium compound catalysts, iridium compound catalysts, nickel compound catalysts, cobalt compound catalysts, iron compound catalysts, etc. Among these, platinum compound-containing catalysts and rhodium compound catalysts are preferred from the viewpoints of availability and reactivity.
[0022] Specific examples of platinum compound-containing catalysts include chloroplatinic acid, alcohol solutions of chloroplatinic acid, toluene or xylene solutions of platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complexes, tetrakistriphenylphosphine platinum, dichlorobistriphenylphosphine platinum, dichlorobisacetonitrile platinum, dichlorobisbenzonitrile platinum, dichlorocyclooctadiene platinum, and the like, as well as supported catalysts such as platinum-carbon, platinum-alumina, and platinum-silica. Among these, from the viewpoint of selectivity during hydrosilylation, zero-valent platinum complexes are preferred, and a toluene or xylene solution of a platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex is preferred. The amount of the platinum compound-containing catalyst used is not particularly limited. However, from the viewpoints of reactivity and productivity, it is preferable that the amount of platinum atoms contained is 1×10 per mole of hydrosilane. -8 ~1×10 -2 The molar amount is preferably 1×10 -7 ~1×10 -3 Molar amounts are more preferred.
[0023] Specific examples of the rhodium compound catalyst include chlorotris(triphenylphosphine)rhodium(I), carbonylchlorobis(triphenylphosphine)rhodium(I), chlorobis(cyclooctene)rhodium(I) dimer, chlorobis(cyclooctene)rhodium(I) dimer, chloro(1,5-hexadiene)rhodium(I) dimer, chloro(1,5-cyclooctadiene)rhodium(I) dimer, and supported catalysts such as rhodium-carbon, rhodium-alumina, and rhodium-silica. Of these, chlorotris(triphenylphosphine)rhodium(I) is preferred. The amount of the rhodium compound catalyst used is not particularly limited. However, from the viewpoints of reactivity and productivity, it is preferable that the amount of the rhodium atom contained is 1×10 -8 ~1×10 -2 The molar amount is preferably 1×10 -7 ~1×10 -3 Molar amounts are more preferred.
[0024] In the above reaction, a co-catalyst may be further used, which is preferably at least one selected from the group consisting of ammonium salts of inorganic acids, acid amide compounds, and carboxylic acids. Specific examples of ammonium salts of inorganic acids include ammonium chloride, ammonium sulfate, ammonium amidosulfate, ammonium nitrate, monoammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium hypophosphite, ammonium carbonate, ammonium hydrogen carbonate, ammonium sulfide, ammonium borate, and ammonium fluoroborate. Among these, ammonium salts of inorganic acids having a pKa of 2 or more are preferred, and ammonium carbonate and ammonium hydrogen carbonate are more preferred.
[0025] Specific examples of acid amide compounds include formamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, propionamide, acrylamide, malonamide, succinamide, maleamide, fumaramide, benzamide, phthalamide, palmitic acid amide, and stearic acid amide, and among these, formamide is more preferred.
[0026] Specific examples of carboxylic acids include formic acid, acetic acid, propionic acid, butyric acid, methoxyacetic acid, pentanoic acid, caproic acid, heptanoic acid, octanoic acid, lactic acid, and glycolic acid. Among these, formic acid, acetic acid, and lactic acid are preferred, and acetic acid is more preferred.
[0027] When a cocatalyst is used, the amount of the cocatalyst used is not particularly limited. However, from the viewpoints of reactivity, selectivity, cost, etc., it is preferable to use a cocatalyst in an amount of 1×10 -5~5×10 -1 Molar is preferred, 1 x 10 -4 ~1×10 -1 Molar is more preferred.
[0028] The above reaction proceeds without a solvent, but a solvent can also be used. Specific examples of usable solvents include hydrocarbon solvents such as pentane, hexane, cyclohexane, heptane, isooctane, benzene, toluene, and xylene; ether solvents such as diethyl ether, tetrahydrofuran, and dioxane; ester solvents such as ethyl acetate and butyl acetate; aprotic polar solvents such as N,N-dimethylformamide; and chlorinated hydrocarbon solvents such as dichloromethane and chloroform. These solvents may be used alone or in combination of two or more.
[0029] The reaction temperature in the above reaction is not particularly limited, and the reaction can be carried out from 0°C under heating, preferably 0 to 200°C. In order to obtain an appropriate reaction rate, it is preferable to carry out the reaction under heating. From this viewpoint, the reaction temperature is more preferably 40 to 110°C, and even more preferably 40 to 90°C. The reaction time is not particularly limited and is usually about 1 to 60 hours, preferably 1 to 30 hours, and more preferably 1 to 20 hours.
[0030] (2) Base material The substrate used in the article of the present invention is not particularly limited, but is preferably an inorganic material, and specific examples thereof include inorganic particles (inorganic fillers) such as silica, titania, zirconia, calcium carbonate, magnesium carbonate, alumina, magnesium oxide, aluminum hydroxide, magnesium hydroxide, talc, clay, and mica; glass fibers such as monofilaments, glass strands, glass yarns, glass rovings, twisted yarns, bulky processed yarns, chopped strands, milled fibers, staple fibers, glass cloth, nonwoven fabrics, tapes, and nets; ceramics such as pottery, cement, enamel, and fine ceramics; and metals such as iron, aluminum, copper, silver, gold, and magnesium. Among these, silica particles or glass fibers are particularly preferred from the viewpoint of the reactivity of the alkoxysilyl group.
[0031] (2-1) Silica particles The silica particles are not particularly limited, and examples thereof include colloidal silica, fumed silica, crystalline silica, and fused silica. In the case of colloidal silica, the silica particles are preferably colloidally dispersed in a medium such as water or an organic solvent, and commercially available water-dispersed or organic-dispersed types can be used. The shape of the silica particles is not particularly limited, and examples thereof include spherical and irregular shapes, but spherical shapes are preferred, and the average particle size is also not particularly limited, but a median size measured by dynamic light scattering is preferably 1 to 100 nm. As such silica particles, commercially available products can be used, and examples thereof include Snowtex O, OS, O40, OL, methanol silica sol, IPA-ST, IBA-ST, PMA-ST, MEK-ST, and the like manufactured by Nissan Chemical Industries, Ltd., and among these, Snowtex O is preferred.
[0032] (2-2) Glass fiber As the glass fiber, glass cloth is preferred. The glass yarn constituting the glass cloth that is the substrate before surface treatment is not particularly limited, and glass compositions of known glass compositions can be used. Specific examples thereof include E glass, L glass, L2 glass, NE glass, NE2 glass, S glass, T glass, UT glass, LU glass, D glass, silica glass, etc., and one or more types of glass cloth selected from the group consisting of these glasses are used depending on the application. Among these, glass cloth selected from L glass, L2 glass, NE glass, NE2 glass, LU glass, and silica glass is preferred in terms of dielectric properties. In the present invention, the dielectric loss tangent at 10 GHz refers to a value measured by the method described in JIS R 1641:2007 (Method for measuring microwave dielectric properties of fine ceramic substrates).
[0033] It is preferable to remove organic substances such as a sizing agent attached to the surface of the glass cloth before surface treatment with the organosilicon compound, since the surface of the glass cloth can be treated evenly with the organosilicon compound. Methods for removing the organic substances include heat cleaning treatment, corona treatment, and hot water washing treatment.
[0034] The thickness of the glass cloth is preferably 6 to 200 μm, more preferably 10 to 100 μm, and the mass per unit area is preferably 5 to 200 g / m 2 and 10 to 100 g / m 2 The glass cloth is more preferable.
[0035] (3) Manufacturing method of the article The article of the present invention includes a substrate that has been surface-treated as described above. It is preferable that the surface-treated substrate itself is used as the article. In this case, the method for producing the article of the present invention is not particularly limited, and the article of the present invention can be produced by appropriately selecting a surface treatment method for the substrate depending on the type, shape, etc. of the substrate.
[0036] (3-1) Method for producing surface-treated silica particles When silica particles are used as the substrate, for example, a method of surface treatment in a solvent may be used. When a resin is used in a post-process, a kneading treatment in which compound (1) is added to and mixed with a compound consisting of untreated silica particles and a resin dispersion medium may be used. However, the method of surface treatment in a solvent is preferred. The solvent may be one that is generally easily available, and examples thereof include water; alcohol-based solvents such as methanol, ethanol, and isopropyl alcohol; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; hydrocarbon-based solvents such as hexane, toluene, and xylene; ether-based solvents such as diethyl ether, tetrahydrofuran, and dioxane; and ester-based solvents such as ethyl acetate and butyl acetate. One type of solvent may be used alone, or two or more types may be mixed and used.
[0037] In the present invention, it is preferable to use a colloidal silica dispersion in which silica particles are dispersed in the above-mentioned solvent, and the compounds (1) to (7) can be added to this dispersion, and the surface treatment can be performed by mixing and stirring. The treatment conditions are not particularly limited, but can be, for example, preferably 20 to 150°C, more preferably 25 to 120°C, and preferably 1 to 10 hours, more preferably 1 to 6 hours.
[0038] The total amount of the compounds (1) to (7) added is preferably 1 to 50 parts by mass, and more preferably 5 to 20 parts by mass, per 100 parts by mass of the silica particles.
[0039] In the surface treatment of the silica particles, organosilicon compounds other than the compounds (1) to (7), such as alkoxy group-containing organosilicon compounds and silazane structure-containing compounds, may be used in combination. Specific examples of the alkoxy group-containing organosilicon compound include 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, p-styryltrimethoxysilane, and 8-methacryloxyoctyltrimethoxysilane. Specific examples of the silazane structure-containing compound include low-molecular-weight silazane compounds such as 1,1,3,3-tetramethyldisilazane, hexamethyldisilazane, 1,3-divinyl-1,1,3,3-tetramethyldisilazane, octamethyltrisilazane, 1,1,3,3,5,5-hexamethylcyclotrisilazane, and 1,1,3,3,5,5-trimethyltrivinylcyclotrisilazane. These may be used alone or in combination of two or more.
[0040] When an organosilicon compound other than the compounds (1) to (7) is used, it may be added simultaneously with the compounds (1) to (7), or it may be added before or after the surface treatment with the compounds (1) to (7). However, it is preferable to add it after the surface treatment with the compounds (1) to (7). When an organosilicon compound other than the compounds (1) to (7) is used, the total amount added is preferably 1 to 50 parts by mass, more preferably 5 to 20 parts by mass, per 100 parts by mass of the silica particles.
[0041] After the surface treatment, the solvent is removed by a separation means such as filtration or liquid separation, and the particles are washed and dried to obtain surface-treated silica particles. The drying conditions are not particularly limited, but are preferably 60 to 180°C, more preferably 80 to 150°C, and are preferably 5 minutes to 2 hours, more preferably 10 minutes to 1 hour, for example. The above production method can be similarly applied to inorganic particles and inorganic fillers other than silica particles.
[0042] (3-2) Manufacturing method of surface-treated glass fiber When glass fibers are used as the substrate, glass cloth is particularly preferred. When the surface of the glass cloth is treated, it can be treated with an aqueous solution in which one or more of the organosilicon compounds represented by the formulas (1) to (7) are dissolved in water. The surface treatment method of the glass cloth is not particularly limited, but specifically, flow coating (immersion method), spin coating, etc. can be mentioned as a method for directly treating the substrate, and other known methods such as spray coating, dip coating, roller coating, brush coating, bar coating, etc. can be appropriately selected and used. After treatment with an aqueous solution, it is preferable to perform a heating and drying treatment. Representative heating and drying conditions include, for example, heating and drying at 60 to 180°C, preferably 80 to 150°C, for 5 minutes to 2 hours, and it is preferable to remove the solvent and simultaneously chemically react the organosilicon compound in the solution with the substrate surface. The above manufacturing method can be similarly applied to substrates other than glass cloth.
[0043] [Aqueous solution] In the aqueous solution of the present invention, the compounds (1) to (7) are dissolved in water. The total content of the compounds (1) to (7) in the aqueous solution is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass, of the entire aqueous solution. The aqueous solution of the present invention can be prepared by mixing the compounds (1) to (7) with water and dissolving the compounds (1) to (7) in water. In this case, the compounds may be added to the water or the water may be added to the compounds, but the method of adding the compounds to the water is preferred, and the method of dropping the compounds into the water is more preferred. The addition temperature is preferably from 10 to 50°C, more preferably from 15 to 40°C.
[0044] An organic solvent may be added to the aqueous solution of the present invention for the purpose of improving handling properties, storage stability, coating properties, etc. The organic solvent is not particularly limited, but is preferably an organic solvent having excellent compatibility with water, and examples thereof include alcohols such as methanol, ethanol, isopropanol, etc.; ethers such as diethyl ether, tetrahydrofuran, 1,4-dioxane, etc.; esters such as ethyl acetate, etc.; ketones such as acetone, methyl ethyl ketone, etc., and one type may be used alone, or two or more types may be used in combination.
[0045] When the above organic solvent is not used, it is preferable to use water adjusted to be acidic from the viewpoint of stability in the aqueous solution of the present invention. Examples of the acid to be used for adjusting the acidity include organic acids such as formic acid, acetic acid, and citric acid, and inorganic acids such as hydrochloric acid. When an acid is used, the amount of the acid added is preferably 0.001 to 0.5% by mass, more preferably 0.01 to 0.1% by mass, of the total aqueous solution. When an acid is used, the water may be adjusted to be acidic by mixing the acid with water in advance, or the aqueous solution containing the compounds (1) to (7) may be adjusted to be acidic by adding the acid thereto.
[0046] To the aqueous solution of the present invention, an alkoxy group-containing organosilicon compound or a silazane structure-containing compound other than the compounds (1) to (7) may be added as necessary to improve adhesion and bonding to the substrate, within a range that does not impair the effects of the present invention. Specific examples of the alkoxy group-containing organosilicon compound and the silazane structure-containing compound include the same as those exemplified in the method for producing surface-treated silica particles. When an alkoxy group-containing organosilicon compound or a silazane structure-containing compound is used, the amount added is preferably 0.01 to 0.2 mol per 1 mol of the total of the compounds (1) to (7).
[0047] In addition, various additives can be added to the aqueous solution of the present invention as necessary within the range that does not impair the effects of the present invention. Specific examples of additives include water-soluble resins, curing catalysts, physical property adjusters that adjust the tensile properties of the resulting cured coating, storage stability improvers, surfactants, metal deactivators, antiozonants, lubricants, pigments, etc.
[0048] The aqueous solution of the present invention can be suitably used as a glass cloth treatment solution.
[0049] [Prepreg] The prepreg of the present invention comprises the above-mentioned article and a matrix resin. The article containing the substrate surface-treated with the organosilicon compound of the present invention can be mixed with a matrix resin to form a prepreg. In particular, when the substrate (article) is surface-treated silica particles or surface-treated glass cloth, the resulting prepreg has excellent strength and can be suitably used, for example, for printed wiring boards.
[0050] (1)Goods The article contained in the prepreg is not particularly limited as long as it contains a substrate that has been surface-treated with the organosilicon compound of the present invention. However, it is preferable that the substrate itself is a surface-treated substrate, such as the above-mentioned surface-treated silica particles or surface-treated glass cloth.
[0051] (2) Matrix resin The matrix resin in the present invention is impregnated into the glass cloth for low dielectric materials to form a prepreg, and either a thermosetting resin or a thermoplastic resin can be used. In particular, a resin having low dielectric properties is preferred, and one or more resins selected from epoxy resin, silicone resin, polyimide resin, bismaleimide resin, polyphenylene ether resin, and polytetrafluoroethylene resin are more preferred. The matrix resin may be used alone or in combination with a plurality of resins. Furthermore, resins other than the matrix resin can be used, but resins with excellent dielectric properties are preferred. In order to manufacture a prepreg for a high-frequency board having excellent dielectric properties, it is preferred that the matrix resin also has excellent dielectric properties, and among these, polyphenylene ether resin is preferred.
[0052] Other components may be added to the matrix resin in the present invention in order to accelerate the curing of the resin, increase the strength, etc. Specific examples of other components include inorganic fillers, flame retardants, additives, reaction initiators, crosslinking agents, curing agents, organic resins other than the matrix resin, etc. When other components are blended, the amount added is preferably 1 to 900 parts by mass, more preferably 10 to 500 parts by mass, and even more preferably 10 to 100 parts by mass, relative to 100 parts by mass of the matrix resin.
[0053] (3) Manufacturing method of prepreg The method for producing the prepreg of the present invention is not particularly limited, and general methods for producing glass cloth-containing substrates, films, prepregs, etc. can be applied. For example, a method in which a molten matrix resin or a solution containing a matrix resin is mixed with a surface-treated inorganic filler, and the obtained resin is applied to a glass cloth to impregnate it, or a method in which a matrix resin is applied to a surface-treated glass cloth to impregnate it, etc. can be used.
[0054] (3-1) Method for producing prepreg containing surface-treated silica particles When surface-treated silica particles are used as the article, a prepreg containing the surface-treated silica particles can be obtained by mixing a matrix resin, the surface-treated silica particles, and other components as necessary, and applying the resulting resin to a glass cloth and impregnating it therewith.
[0055] To improve and ensure the coating property, the matrix resin may be diluted with a solvent. Depending on the solubility property of the matrix resin, one organic solvent may be used alone or two or more organic solvents may be used in combination. Examples of organic solvents include alcohols such as methanol, ethanol, isopropanol, and n-butanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; glycol ethers such as ethylene glycol and propylene glycol; aliphatic hydrocarbons such as hexane and heptane; aromatic hydrocarbons such as toluene and xylene; and alkyl ethers such as diethyl ether, diisopropyl ether, and dibutyl ether.
[0056] The method for mixing the matrix resin and the surface-treated silica particles is not particularly limited, but examples include a method in which the matrix resin or a solution containing the matrix resin, the surface-treated silica particles, and other components, if necessary, are mixed by a conventionally known method and stirred for about 10 minutes to 1 hour.
[0057] The amount of the surface-treated silica particles added is preferably 10 to 300 parts by mass, more preferably 50 to 200 parts by mass, and even more preferably 60 to 150 parts by mass, per 100 parts by mass of the matrix resin (the amount of matrix resin contained in the case of a solution). The glass cloth may be surface-untreated or surface-treated, and one type may be used alone or two or more types may be used in combination.
[0058] Next, the matrix resin containing the surface-treated silica particles is applied to the glass cloth and impregnated therein. The prepreg of the present invention can be produced, for example, in accordance with a general method for applying a curable resin composition to glass cloth fibers (coating method). Representative coating methods include direct gravure coater, chamber doctor coater, offset gravure coater, single roll kiss coater, reverse kiss coater, bar coater, reverse roll coater, slotter die, air doctor coater, positive rotation roll coater, blade coater, knife coater, impregnation coater, MB coater, MB reverse coater, etc.
[0059] The amount of the matrix resin attached to the glass cloth is preferably 10 to 80% by mass, more preferably 20 to 70% by mass. Within this range, the amount of the matrix resin attached to the glass cloth is appropriate, and there is an effect of improving the adhesion and bonding with the matrix resin, and the strength of the wiring board. If the amount of the matrix resin attached is 10% by mass or more, when the prepreg and the copper foil are laminated to produce a board, the amount of the matrix resin attached to the copper foil is not too small, and sufficient peel strength with the copper foil can be obtained. In addition, if the amount of the matrix resin attached is 80% by mass or less, the amount of the matrix resin is not too large, and resin flow during pressing is unlikely to occur, which is preferable. The amount of the matrix resin attached here indicates the mass % of the matrix resin relative to the mass of the entire prepreg.
[0060] Conditions vary depending on the matrix resin used, but for example, after application, the resin can be dried and then heated at 50 to 300° C. for 1 minute to 24 hours for curing.
[0061] (3-2) Method for manufacturing prepreg containing surface-treated glass cloth The glass cloth surface-treated with the aqueous solution of the present invention is suitably used for producing a prepreg by impregnating the surface-treated glass cloth with a matrix resin. When a surface-treated glass cloth is used as the article, a prepreg containing the surface-treated glass cloth can be obtained by mixing a matrix resin or a solution containing a matrix resin with other components as necessary and impregnating the surface-treated glass cloth with the obtained resin or solution. The specific manufacturing method is the same as that in the case of using surface-treated silica particles. Surface-treated silica particles may be added to the matrix resin, and in that case, the amount added is the same as above.
[0062] The thickness of the prepreg of the present invention is not particularly limited, but is preferably 10 to 400 μm, more preferably 30 to 300 μm, and even more preferably 40 to 200 μm. Within this range, for example, when the prepreg of the present invention is used for a printed wiring board, a board such as a copper-clad laminate can be well prepared. The prepreg of the present invention may be semi-cured (B-staged) in advance by heating. There are no particular limitations on the method for B-staging, but for example, the matrix resin may be dissolved in a solvent, impregnated into glass cloth, dried, and then heated at a temperature of 80 to 200°C for 1 to 30 minutes to achieve B-stage.
[0063] [Printed wiring board] The printed wiring board of the present invention comprises the above-mentioned prepreg. The method for producing the printed wiring board of the present invention is not particularly limited, and a general method for producing a printed wiring board can be applied. Specifically, the printed wiring board can be produced by, for example, laminating one or more sheets, preferably 2 to 20 sheets, of the prepreg, and heat curing the laminate. In addition, the prepreg of the present invention and a copper foil are stacked, pressed, and heat-cured to produce a copper-clad laminate. There is no particular limitation on the method for producing the copper-clad laminate, but it can be produced, for example, by stacking the prepreg in the same manner as above, arranging copper foil on one or both sides of the laminate, pressing, and heat-curing.
[0064] The thickness of the copper foil is not particularly limited, but is preferably 3 to 70 μm, more preferably 10 to 50 μm, and even more preferably 15 to 40 μm. Within this range, a multi-layer copper-clad laminate with high reliability can be formed. In addition, the prepreg of the present invention, the copper foil, and the inner layer wiring board can be combined and molded to form a copper-clad laminate. The heat curing conditions are, for example, heating at 100 to 250° C. for 1 to 600 minutes, and if necessary, a pressure of 0.1 to 20 MPa may be applied simultaneously with heating.
[0065] The glass cloth and surface-treated silica particles surface-treated with the aqueous solution of the present invention provide prepregs and printed wiring boards that have excellent adhesion and bonding properties with matrix resins and have improved strength and higher reliability, and can therefore be suitably used as materials for insulating layers and the like of electronic components having circuits that transmit electrical signals of 10 GHz or more, particularly millimeter waves, for high-speed servers and the like.
[0066] The method of circuit processing is not particularly limited, and examples thereof include circuit formation processing methods such as drilling, metal plating, etching of metal foil, etc. In addition, a printed wiring board may be produced by a build-up method in which a composition containing a matrix resin or the prepreg of the present invention and copper foil are sequentially laminated. EXAMPLES
[0067] The present invention will be described more specifically below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0068] [1] Synthesis of organosilicon compounds [Synthesis Example 1] In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 0.55g of chlorotris(triphenylphosphine)rhodium(I), 300.0g of toluene, 0.3g of 2,6-di-t-butyl-p-cresol and 0.1g of tetrabutylammonium bromide were placed, and 125.4g (1.84 mol) of isoprene and 150.0g (1.23 mol) of trimethoxyhydrosilane were added dropwise at an internal temperature of 60-70°C over 2 hours. The mixture was then stirred at 60°C for 5 hours, and analyzed by gas chromatography, confirming the disappearance of trimethoxyhydrosilane. The resulting solution was purified by distillation at 20mmHg and 80°C to obtain a kinetic viscosity of 1.2mm. 2 Thus, 180 g of a colorless, transparent liquid (organosilicon compound 1) having a refractive index of 1.420 was obtained. 1 1 H-NMR measurement and gas chromatography mass spectrometry (GC / MS) measurement confirmed that the obtained organosilicon compound 1 was a mixture of compounds represented by the following formulas (8) to (14).
[0069] [ka]
[0070] In the above examples, the kinematic viscosity and refractive index were measured at 25°C. In this case, the kinematic viscosity was measured based on JIS Z 8803. The refractive index was measured in accordance with JIS K 0062. Nuclear magnetic resonance spectrum ( 1 H-NMR measurements were performed in deuterated chloroform using an AVANCE III / ULTRASIELD 400 manufactured by BRUKER. Gas chromatography (GC) analysis was carried out under the following measurement conditions. GC equipment: Agilent Technologies 6890N Detector: Flame ionization detector (FID) Column: HP-5 J-413 (length 30 m × inner diameter 0.32 mm, film thickness 0.25 μm) Column temperature: 50°C → 10°C / min → 300°C (10 min hold) Inlet temperature: 250℃ Detector temperature: 300℃ Carrier gas: He Carrier gas flow rate: 1.0mL / min Gas chromatography mass spectrometry (GC / MS) measurements were performed under the following conditions. GC equipment: Agilent Technologies 7200 Q-TOF GC / MS Detector: FID & TTOF-MS Column: HP-5 S-433 (length 30 m x inner diameter 0.25 mm, film thickness 0.25 μm) Column temperature: 50°C → 10°C / min → 280°C (10 min hold) Inlet temperature: 250℃ Detector temperature: 300℃ Carrier gas: He Carrier gas flow rate: 30mL / min Ionization method: EI Ion source temperature: 250℃ Mass range: m / z=30-1000
[0071] [2] Preparation of aqueous solution [Example 1-1, Comparative Examples 1-1 and 1-2] According to the formulation in Table 1, ion-exchanged water and acetic acid were mixed and stirred, and organosilicon compound 1 obtained in Synthesis Example 1 above, organosilicon compound 2 below, or organosilicon compound 3 below was added dropwise to prepare an aqueous solution. The aqueous solutions thus obtained were subjected to the following evaluations, and the results are shown in Table 1.
[0072] Organosilicon compound 2: 5-hexenyltrimethoxysilane (product name: KBM-1063, manufactured by Shin-Etsu Chemical Co., Ltd.) Organosilicon compound 3: 7-octenyltrimethoxysilane (product name: KBM-1083, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0073] [Stability of aqueous solution] The resulting aqueous solutions were allowed to stand in an environment of 25° C. for 1 day and 14 days, and then the appearances were visually inspected and evaluated according to the following criteria. ◯: Completely dissolved, forming a homogeneous aqueous solution. ×: Insoluble matter precipitated.
[0074] [Table 1]
[0075] As shown in Table 1, in Example 1-1 in which organosilicon compound 1 obtained in Synthesis Example 1 was used, the stability of the aqueous solution was good.
[0076] [3] Manufacturing of surface-treated silica particles [Example 2-1] 625 g of silica sol obtained by concentrating a silica concentration of a commercially available acidic aqueous silica sol (trade name: Snowtex O, manufactured by Nissan Chemical Industries, Ltd.) to 40% by mass, and 1125 g of isopropyl alcohol were stirred at room temperature while bubbling air in a 2-liter glass separable flask equipped with a stirrer, a dropping funnel, a cooling tube, and a thermometer. 30 g of the organosilicon compound 1 obtained in the above Synthesis Example 1 was dropped into the flask, and the temperature was raised to 78°C and stirring was continued for 4 hours to perform a hydrophobic treatment of the silica sol. Thereafter, the internal temperature was lowered to 70°C, and 34 g of hexamethyldisilazane (trade name: HMDS, manufactured by Shin-Etsu Chemical Co., Ltd.) was dropped, and stirring was continued for 2 hours. The solvent of the obtained silica dispersion was filtered, washed with methanol, and then dried at 110°C under reduced pressure for 1 hour to obtain silica particles (A) surface-treated with the organosilicon compound 1.
[0077] [Comparative Example 2-1] In Example 2-1, the same operation as in Example 2-1 was carried out except that 28 g of organosilicon compound 4 (vinyltrimethoxysilane, product name: KBM-1003, manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of organosilicon compound 1, thereby obtaining surface-treated silica particles (B).
[0078] [4] Manufacturing of prepregs and substrates using surface-treated silica particles [Examples 3-1, 3-2, Comparative Examples 3-1 to 3-3] A polyphenylene ether resin containing methacryloxy groups as polymerizable reactive groups (Noryl (registered trademark) SA9000 manufactured by SHPP Japan LLC, hereafter referred to as PPE) was mixed with toluene in a mass ratio of 1:1, and the mixed solution was heated and stirred at 80°C for 1 hour to completely dissolve the PPE in the toluene, and then cooled to 25°C to obtain a 50% by mass toluene solution of PPE. Next, according to the blending ratios (parts by mass) shown in Table 2, a 50% by mass toluene solution of the above PPE (the blending amounts in Table 2 are values calculated based on the non-volatile content of PPE), a crosslinking agent, an organic resin, surface-treated silica particles, and a curing agent were mixed and stirred for 30 minutes to completely dissolve, thereby obtaining a varnish-like curable composition (resin varnish).
[0079] Next, the obtained resin varnish was impregnated into a glass cloth (manufactured by Nitto Boseki Co., Ltd., #1078 type, WEA1078), and then heated and dried at 120° C. for 3 minutes to obtain a prepreg. At this time, the thickness after curing was adjusted to be about 60 μm. Both sides of one of the obtained prepregs were sandwiched between copper foil (GT-MP manufactured by Furukawa Electric Co., Ltd., thickness 12 μm) and laminated, and then sintered under vacuum conditions at 220°C for 90 minutes at a pressure of 40 kgf / cm. 2 By applying heat and pressure under the above conditions, an evaluation substrate 1 was obtained. In addition, 12 sheets of the prepreg obtained above were stacked, sandwiched between copper foil (GT-MP manufactured by Furukawa Electric Co., Ltd., thickness 12 μm), and laminated under vacuum conditions at 220°C for 90 minutes and a pressure of 40 kgf / cm. 2 By applying heat and pressure under the above conditions, an evaluation substrate 2 was obtained.
[0080] The evaluation substrates 1 and 2 prepared by the above procedure were evaluated by the methods described below. The results are shown in Table 2 below. [Dielectric properties] The copper foil was removed from the evaluation board 2 produced above, and the relative dielectric constant and the dielectric loss tangent at 10 GHz were measured using a network analyzer (Keysight Corp.: E5063-2D5) by the cavity resonator perturbation method. [Copper foil adhesion strength] The peel strength (copper foil adhesion strength) of the evaluation board 1 prepared above was measured by a method conforming to JIS C 6481. At this time, a pattern with a width of 10 mm and a length of 100 mm was formed on a test piece with a width of 20 mm and a length of 100 mm, and the copper foil was peeled off at a speed of 50 mm / min using a tensile tester, and the peel strength (kN / m) at this time was evaluated as the copper foil adhesion strength.
[0081] [Table 2]
[0082] Each component shown in Table 2 will be explained below. PPE: PPO Noryl (registered trademark) SA9000 (polyphenylene ether resin containing methacryloxy groups as polymerizable reactive groups) manufactured by SABIC Innovative Plastics Co., Ltd. (SHPP Japan LLC) Crosslinking agent 1: DCP (tricyclodecane dimethanol dimethacrylate) manufactured by Shin-Nakamura Chemical Co., Ltd. Crosslinking agent 2: TAIC (trademark) (triallyl isocyanurate) manufactured by Nippon Kasei Co., Ltd. Organic resin: Cray Valley Ricon 156 (polybutadiene) Hardener: NOF Corp. Perbutyl P (1,3-bis(butylperoxyisopropyl)benzene, peroxide)
[0083] As shown in Table 2, the printed wiring board having a prepreg using silica particles surface-treated with the organosilicon compound of the present invention has excellent dielectric properties and copper foil adhesion strength.
[0084] [5] Manufacturing of surface-treated glass cloth [Example 4-1, Comparative Examples 4-1 to 4-5] A glass cloth treatment solution was prepared according to the following procedure, and the glass cloth was subjected to surface treatment. The above organosilicon compound 1, the above organosilicon compound 4 (vinyltrimethoxysilane, product name: KBM-1003, manufactured by Shin-Etsu Chemical Co., Ltd.), or the following organosilicon compound 6 was added to a 0.1% by mass aqueous acetic acid solution to a concentration of 0.2% by mass and stirred to prepare a glass cloth treatment liquid containing the above organosilicon compound 1, the above organosilicon compound 4, or the following organosilicon compound 6. In addition, organosilicon compound 5 or organosilicon compound 7 shown below was added to ion-exchanged water to a concentration of 0.2 mass % and stirred to prepare a glass cloth treatment liquid containing organosilicon compound 5 or organosilicon compound 7 shown below. The obtained glass cloth treatment liquid was added to a silica glass cloth (thickness: 95 μm, mass per unit area: 93 g / m 2 ) and then heated and dried at 110°C for 10 minutes to produce a surface-treated glass cloth.
[0085] Organosilicon compound 5: 3-aminopropyltrimethoxysilane (product name: KBM-903, manufactured by Shin-Etsu Chemical Co., Ltd.) Organosilicon compound 6: 3-(methacryloyloxy)propyltrimethoxysilane (product name: KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) Organosilicon compound 7: N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride (trade name: KBM-575, Shin-Etsu Chemical Co., Ltd.)
[0086] The obtained surface-treated glass cloth was evaluated by the following methods, and the results are shown in Table 3 below.
[0087] [Dielectric properties] A rectangular molded piece of 3 cm x 4 cm with a thickness of 0.15 mm was prepared. A network analyzer (Keysight: E5063-2D5) was connected to a strip line (Keycom Co., Ltd.) to measure the dielectric constant and dielectric loss tangent of the molded piece at a frequency of 10 GHz. The measurement results of a glass cloth that was not surface-treated (Comparative Example 4-1) were converted to 100 and evaluation was performed.
[0088] [6] Manufacturing of prepregs and substrates using surface-treated glass cloth [Example 5-1, Comparative Examples 5-1 to 5-5] The surface-treated glass cloth obtained in Example 4-1 and Comparative Examples 4-1 to 4-5 was impregnated with a matrix resin (M-1), and the prepreg was obtained by removing the solvent by heating and drying at 100°C for 10 minutes. Next, one prepreg was heat-cured at 180°C for 60 minutes under a pressure of 5 MPa using a vacuum press to produce an evaluation substrate 3. In Comparative Example 5-1, evaluation substrate 3 was produced in the same manner as in the other Examples and Comparative Examples, except that an untreated silica glass cloth was used. Here, the matrix resin (M-1) is a mixture of 100 parts by mass of a bismaleimide compound (product name: BMI-5000P, manufactured by Designer Molecules Inc.) and 122 parts by mass of toluene (resin concentration: 45% by mass), to which 2 parts by mass of dicumyl peroxide was added as a curing catalyst.
[0089] Each of the obtained evaluation substrates 3 was evaluated by the following method. The results are shown in Table 3 below.
[0090] [Dielectric properties] As with the above-mentioned surface-treated glass cloth, the relative dielectric constant and dielectric tangent of each evaluation substrate 3 were measured, and the measurement results of a printed wiring board (Comparative Example 5-1) using a glass cloth that had not been surface-treated (Comparative Example 4-1) were converted to 100, and the evaluation was performed.
[0091] [Tensile strength] The tensile strength of the evaluation substrate 3 was measured in accordance with JIS K 6251:2010 using EZ TEST (EZ-L, manufactured by Shimadzu Corporation) under conditions of a test speed of 500 mm / min, a gripping distance of 80 mm, and a gauge length of 40 mm.
[0092] [Table 3]
[0093] As shown in Table 3, the substrate using the surface-treated glass cloth of Example 4-1 (Example 5-1) had excellent tensile strength without deteriorating the dielectric properties. On the other hand, the substrate using the glass cloth treated with vinyltrimethoxysilane (Comparative Example 4-2) (Comparative Example 5-2) had poor tensile strength. This is believed to be because the organosilicon compound has a small number of carbon atoms and is therefore poorly compatible with the matrix resin. In addition, it was confirmed that the dielectric properties were deteriorated when glass cloth surface-treated with an organosilicon compound having oxygen or nitrogen atoms (Comparative Examples 5-3 to 5-5) was used.
Claims
1. An article comprising a substrate whose surface has been treated with one or more organosilicon compounds selected from those represented by the following formulas (1) to (7): 【Chemistry 1】 (In the formula, R 1 are each independently an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms; R 2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an acyl group having 1 to 20 carbon atoms, and n is an integer of 0 to 2.
2. 2. The article of claim 1, wherein the substrate is an inorganic material.
3. 3. The article of claim 2, wherein the inorganic material is silica particles or glass fibers.
4. A prepreg comprising the article of claim 3 and a matrix resin.
5. A printed wiring board comprising the prepreg according to claim 4.
6. An aqueous solution in which one or more organic silicon compounds selected from the group consisting of those represented by the following formulas (1) to (7) are dissolved in water: 【Chemistry 2】 (In the formula, R 1 are each independently an alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms; R 2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an acyl group having 1 to 20 carbon atoms, and n is an integer of 0 to 2.
Citation Information
Patent Citations
Production of acyloxysilane compound having functional group bonded with silicon atom through silicon-carbon bond
JP2000086676A
Toner additive containing composite material particles
JP2015502567A
Glass cloth, prepreg, and printed wiring board
JP7015972B1
Method for separating substances
WO2004031757A1
Glass cloth, prepreg and printed wiring board
JP2018127747A